Reading Queer A/theology into Rabih Alameddine’s Koolaids - Shannahan, Dervla (Feminist theology, 2011)
This paper explores Rabih Alameddine’s debut novel, Koolaids, from a queer a/theological perspective. It has been read as portraying an exilic in-betweenness and this paper looks at how this indeterminacy manifests in the text’s relationships to sexuality and Scripture. It argues that Alameddine dissects the stability of sexual norms and desires, and effectively queeries all compulsions to identify. It also discusses how Alameddine rereads and returns to Scripture, whilst rebuking blind faith in anything, and suggests that whilst his own relationship to theologies may be non-committal and ambiguous, the text embodies and exposes multiple possibilities for reconciling queerness of all kinds with Divine and self acceptance. It concludes with the suggestion that Koolaids can be read as offering myriad resources for theological reflection, resources that are at once a/theological, queerly positioned, and ever-open to diverse theological dreamscapes.